A Factual Model for Financial Management in Private High Schools in Semarang, Indonesia - Pendriana, Yuli; Raharjo, Tri Joko; Pramono, Suwito Eko; Yulianto, Arief; Ismail, Mohd Hasmadi (Journal of Ecohumanism, 2025)
In Indonesia, many school principals and education personnel across various education levels demonstrate a lack of the knowledge and competencies needed to effectively manage school finances. This lack of knowledge and competencies manifests in school outcomes across the country. This study aims to identify and develop a practical and empirically-based factual model of financial management for private schools that receive subsidies from the Regional Budget (APBD), particularly through the Regional School Operational Assistance (BOSDA) program. The model was designed as an alternative framework based on real-world financial management practices in private high schools in Semarang, Indonesia. Purposive sampling was used to select respondents. Data were collected through semi-structured interviews and document analysis. The results revealed that some financial management issues in schools appeared to evade supervision, despite the sampled schools having prepared financial reports in accordance with regulations. However, the analysis identified several components that were still not compliant. Nonetheless, this study provides valuable theoretical and practical implications for authorities responsible for overseeing financial management in private schools.